Swine industry stakeholders' perception on the use of water-based foam as an emergency mass depopulation method. - Ting-Yu Cheng; Magnus R Campler; Josie M Rudolphi; Taylor J Williams; Justin D Kieffer; Steven J Moeller; Andrew S Bowman; Andréia G Arruda (PLoS ONE, 2023)
The U.S. pork supply chain is vulnerable to various internal and external threats and in need of prompt, comprehensive response plans. Under urgent circumstances, for example in the case of foreign disease incursions, swine farms will have to perform on-farm animal depopulation to prevent disease spread. Several animal depopulation methods including water-based foam (WBF) have been proposed and are under evaluation for feasibility in the field. However, the psychological/emotional impacts of applying depopulation methods for personnel managing and carrying on the tasks are not currently well understood. Thus, this study aimed to investigate WBF as an alternative for depopulation compared to existing methods approved by the American Veterinary Medical Association. Swine industry stakeholders were invited to voluntarily observe a WBF depopulation trial and to provide their self-reported perspectives before and after the observation. A survey was designed to explore key areas on expected and perceived method effectiveness, efficiency, and animal welfare considerations, as well as to evaluate short-term post-observation psychological impacts. Among 42 recruited stakeholders, 31.0% (13/42) were educators/researchers followed by animal health officials (26.2%, 11/42) and veterinarians (23.8%, 10/42), with an average of 11.7 ± 12.6 (n = 39) years of work experience. After the trial, respondents' positive perception of WBF depopulation increased specifically regarding the animal loading process being less stressful than restrained in-barn depopulation options (P = 0.003) and by the observation of fewer swine escape attempts and vocalizations than expected (P < 0.001). Respondents' positive perception of WBF also increased regarding to the time required to fill the trailer with foam, to stop hearing animal vocalization, and stop hearing animal movement, as the observed trial times were faster than their pre-observation estimates (P < 0.001). Additionally, 79.5% (31/39) of respondents agreed that the rapid destruction of animal populations had priority over animal welfare under urgent scenarios. Minor post-traumatic stress disorder-like (PTSD-like) symptoms from the observed trials were reported (26.7%, 4/15 respondents) one month after the observation. This study showed that the WBF depopulation process was perceived positively by swine stakeholders and may have limited short-term psychological impacts on personnel involved in animal depopulation.